Evaluation of the antimicrobial and antioxidant properties of extracts of Mondia whytei roots extracts - Mayunzu, Oscar; Shitanda, Douglas; Okalebo, Faith; Simiyu, Lidya (Galati University Press, 2011)
Extracts of Mondia whytei (M. whytei) root barks were screened for their inhibitory effects against Staphylococcus aureus (S. aureus) (ATCC 25923), Escherichia coli (E. coli) 0157:H7 (PSSCMI 0032), Bacillus subtilis, Candida albicans and Aspergillus niger were used as test organisms. From the results it was concluded that activity varied with the solvent used. Contrary to previous reports, the plant seems to lack significant antibacterial activity except against E. coli. The popularity of a herbal recipe is not always a measure for its potency. However, M. whytei had antifungal activity since the ethanol and methanol extracts showed significant activity against the tested strains of fungi. The antioxidant activity of the extracts was also evaluated using the DPPH free radical scavenging assay. M. whytei exhibited substantial inhibition of the DPPH activity with EC50 of 413mg/l for the crude extracts. This antioxidant activity of the crude extracts can be attributed to the presence of 2-Hydroxy-4-Methoxybenzaldehyde that is a known antioxidant in the root extracts.
Keywords: Antimicrobial activity; Antioxidant activity; Bioactive plant products